2018
DOI: 10.1126/sciadv.aap9360
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-deficient triple perovskites as highly active and durable bifunctional electrocatalysts for oxygen electrode reactions

Abstract: Triple perovskite, Nd1.5Ba1.5CoFeMnO9−δ, enriched with oxygen defects shows high activity and durability as a bifunctional oxygen electrocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(106 citation statements)
references
References 40 publications
2
99
0
1
Order By: Relevance
“…The Fe-LNO exhibits the highest hydroxyl adsorption capacity nearly 1 : 1, and the hydroxyl adsorption capacity of Fe-LNO is even better than that of pure FeOOH, which is much larger than that of LNO (0.2 : 1), indicating that the modification of FeOOH can greatly optimize the adsorption of hydroxyl. To further determine whether the adsorbents are chemisorption of ∗OH or physisorption of hydroxyl, XPS was used to further prove the adsorption state of hydroxyl [ 55 ], as shown in Figure 3(d) . By comparing the area ratio of the hydroxyl peak and water peak of Fe-LNO and LNO, we found that the adsorption of hydroxyl by Fe-LNO was significantly improved in the range of 2.6 : 1 to 5.0 : 1, implying the generation of a high density of extra oxygen vacancies filled by hydroxyl.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe-LNO exhibits the highest hydroxyl adsorption capacity nearly 1 : 1, and the hydroxyl adsorption capacity of Fe-LNO is even better than that of pure FeOOH, which is much larger than that of LNO (0.2 : 1), indicating that the modification of FeOOH can greatly optimize the adsorption of hydroxyl. To further determine whether the adsorbents are chemisorption of ∗OH or physisorption of hydroxyl, XPS was used to further prove the adsorption state of hydroxyl [ 55 ], as shown in Figure 3(d) . By comparing the area ratio of the hydroxyl peak and water peak of Fe-LNO and LNO, we found that the adsorption of hydroxyl by Fe-LNO was significantly improved in the range of 2.6 : 1 to 5.0 : 1, implying the generation of a high density of extra oxygen vacancies filled by hydroxyl.…”
Section: Resultsmentioning
confidence: 99%
“…Among TMOs, perovskite oxides containing more than one metal have been reported for various applications by virtue of their structural and compositional flexibility 22 , 26 28 . The multiple ions (including metal and oxygen ions) and variable structures of perovskite oxides can bring about some unique electronic and conductive properties, which then modulate the binding energies of reaction intermediates and electron-transport behavior, and consequently their electrocatalytic activities 16 , 22 , 26 , 29 31 . Therefore, designing an ideal perovskite system with multiple catalytic sites, which are tailored for targeting steps in alkaline HER electrocatalysis, may be viable, but still remains a great challenge and yet to be realized.…”
Section: Introductionmentioning
confidence: 99%
“…Structure-activity relationships and relative design principles derived from ex situ findings are often reported. Many typical perovskite families have been exploited to explore their structure-activity relationships and mechanisms, such as single perovskites ABO 3-δ 10 , single-layer Ruddlesden-Popper (RP) perovskites A 2 BO 4-δ 11 , double perovskites A 2 B 2 O 6-δ 12 , triple perovskites A 3 B 3 O 9-δ 13 , three-layer RP perovskites A 4 B 3 O 10-δ 14 , quadruple perovskites A 4 B 4 O 12-δ 15 , and hexagonal perovskites A 8 B 4 O 15-δ 16 . According to these structure-activity correlations obtained from ex situ characterizations and computations, some activity descriptors are also successfully proposed, including e g orbital occupancy 10 , O 2p band center 12 , and charge-transfer energy 17 .…”
mentioning
confidence: 99%